Exploring UX Factors through the Dogfooding Approach: An Experience Report - Damian, Adriana Lopes; Teixeira, Lígia; Carrenho, Cinthia; Ferreira, Bruna; Bentes, Ariel; Tordin, Gustavo; Martin, Graziela; Castro, Lucas; Brotto, Bruna; Pereira, Valéria; Pignatelli, Raquel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
The User Experience (UX) is an important quality attribute for software products, as it addresses aspects related to usage and subjective elements, such as affection, sensations, and emotions. Given its significance, various approaches, methods, and techniques that have been developed to evaluate UX during software development. In this context, Dogfooding is one of the approaches that companies adopt to assess the UX of their products, as seen in companies like Apple and Google. Dogfooding proposes that company employees use their own products or services in their daily lives, allowing them to understand both positive and negative aspects based on user perception. However, it is essential to comprehend how the perceptions reported by users in UX evaluations are analyzed from the viewpoint of UX factors, which encompass characteristics that define such experiences. This article presents the account of an action research aimed at identifying UX factors in the context of mobile devices through the Dogfooding approach. The results revealed different factors that characterize the UX, contributing to a better understanding for teams involved in the development of mobile devices concerning this quality attribute. The identification of these factors guides the creation of new ways to analyze UX in future projects in the context of mobile devices.